Formation and development of ventilated supercavity past the disk–cavitator in accelerated motion - Olena Naumova; Volodymyr Moroz; Viktor Kochin; Volodymyr Semenenko (Mechanics and Advanced Technologies)
The work is devoted to both the experimental studies and the computer simulation of the process of formation and development of a ventilated supercavity past the disk-cavitator in accelerated motion from the state of rest to the steady velocity. A series of experiments were carried out in the high-speed experimental tank at the Institute of Hydromechanics of the National Academy of Sciences of Ukraine for various values of the air-supply rate into the cavity. It has been established that the portion type of air-loss from the cavity is always preserved in the case of horizontal accelerated motion, while the air-loss by vortex tubes is always realized in the case of steady motion with the same velocity. In this case, shape of the cross sections of the unsteady cavity is close to circular one along the whole cavity length and at all stages of acceleration. To describe this process, a modified mathematical model is proposed that is based on the G.V.Logvinovich principle of independence of the cavity section expansion. An analysis of the influence of both the immersion depth and the air-supply rate on the process of development of a ventilated supercavity during acceleration has been performed by the way of computer simulation.